Pengembangan Produk Wisata Berbasis Kharakteristik Wisatawan Prancis di PT. Karang Bali Asli (KBA) Tur Denpasar - Ni Luh Putu Superyadi; I Wayan Wiwin; I Gusti Ngurah Pertu Agung (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2019)
Based on the data from the Bali Provincial Tourism Office in 2018, the number of French tourist visits to Bali continues to increase every year, even in 2018 it occupies the seventh position from the top ten suppliers of tourists to Bali. This condition is inseparablefrom the role of the Travel Agency in Bali, which always innovates and develops tourism products that suit the needs and characteristics of tourists. One of the Travel Agencies that focuses on working on the French tourist market is PT. Karang Bali Asli (KBA) Tour Denpasar which has been operating since 1999. This study examines three problems, namely: (1) What are the tourist characteristics-based products of French tourists offered by PT. KBA Tour ?; (2) What is the perception of French tourists on tourism products offered by PT. KBA Tour ?; and (3) How is the development of tourism products based on the characteristics of French touristsat PT. KBA Tour? This research is a qualitative research, with methods of collecting data through observation, in-depth interviews, questionnaires, and literature studies. The theory used was the Marketing Mix Theory and Perception Theory. The results of the study show that: (1) In general, tourism products offered by PT. KBA Tour Denpasar are interactive tourism products or tourism products that create intractions between tourists with the local community, as well as tourism products that create interaction between tourists and the natural environment; (2) The perception of French tourists on tourism products offered by PT. KBA Tur, shows positive (good) values for the four indicators in the Marketing Mix theory, namely: Product, Price, Place, and Promotion; (3) Business development of tourism products based on the characteristics of French tourists at PT. KBA Tur can be carried out as expected because of thesynergy and support of the local community, company employees, and feedback and input from the tourists themselves, so that the tourism products offered by PT. KBA Tur are very popular with tourists and can be sustainable.